Things don't necessarily go better with coke.. - Unknown (Tufts Archival Research Center, 2018)
The poster has two statements: "Things Don't Necessarily / Go Better with Coke.." and "Don't drink Coke / Support the National Economic Boycott". This is a scan of one of four duplicate posters in the folder.